Laser-generated ultrasound with applications to non-destructive evaluation - Cooper, Jeremy Adrian (1985)
The generation of ultrasound by laser interaction with materials was first studied by White in 1963. Since this time work has been published on both generation in liquids and solids using CW and pulsed lasers. It was first noted by Bondarenko in 1976, that laser generated ultrasound could be applied usefully to non-destructive evaluation (NDE). This method of generation has a major advantage over conventional methods of ultrasonic NDE, which involve the use of piezoelectric transducers acoustically bonded to material surfaces; the laser source is non-contacting giving it a wider range of applications. The present study was undertaken to fully characterise the acoustic source for its use as a new tool in NDE, and to explore some of the potential NDE techniques most suited to the laser-acoustic source. A neodymium/YAG laser has been used to produce pulses of infra-red radiation which then interact with a metal surface to generate ultrasound. Such acoustic disturbances contain fast transients in contrast to conventional piezoelectric transducers. The transient nature of the source allowed a range of accurate "time-of-flight" and imaging techniques to be employed for NDE after first characterising the directional behaviour of the various acoustic modes. In order to fully utilise the acoustic transients it was necessary to use wide bandwidth displacement transducers as acoustic detectors. Ideally these detectors should themselves be non-contacting so that both generation and detection can be carried out remotely. Results have been obtained using a laser interferometer developed by UKAEA, Harwell. However, other investigative work used a modified form of the capacitative type transducer. This capacitance transducer has been developed and characterised and has proved invaluable for the time-of-flight techniques. Using displacement transducers it has been possible to compare acoustic disturbances from different generation mechanisms with displacements predicted by extended theoretical models originally used in seismology. It was found that the laser-acoustic source simulated natural impulsive acoustic emission events and could therefore be used as a diagnostic model in the development of acoustic emission applications. A range of NDE techniques have been investigated: including visualisation of laminar defects with high spatial resolution, depth measurement of surface breaking cracks, thickness measurement of metal foils and plates, and imaging techniques to detect bulk flaws.
Keywords: Applied physics